Erianin induces apoptosis and pyroptosis via MAPK/ERK and PI3K/Akt pathways and synergizes with anlotinib in anaplastic thyroid carcinoma - Zhang, Qiaonan; Qiu, Minghan; Liu, Jinpu; Gao, Zhanhua; Liu, Yuya; Wang, Yayun; Liu, Ruxue; Yang, Zhen; Hao, Jie; Gao, Ming (Frontiers in Pharmacology, 2025)
IntroductionAnaplastic thyroid carcinoma (ATC) is an aggressive thyroid malignancy characterized by rapid progression, resistance to conventional therapies, and poor patient prognosis. There is an urgent need for innovative therapeutic strategies. Erianin, a natural compound derived from Dendrobium, has demonstrated significant anti-tumor effects in various cancers, yet its role in ATC remains unexplored.MethodsThe anti-tumor effects of erianin were assessed in vitro through assays including CCK-8, colony formation, flow cytometry, LDH release, and Western blot. RNA sequencing was conducted for gene expression analysis. Immunofluorescence and transmission electron microscopy evaluated pyroptosis markers. In vivo efficacy was validated in CAL62 xenograft mouse models using tumor growth measurement, TUNEL staining, and immunohistochemistry.ResultsErianin significantly inhibited proliferation and colony formation, induced G2/M cell cycle arrest, apoptosis, and GSDME-dependent pyroptosis in ATC cells. Mechanistically, erianin suppressed activation of the MAPK/ERK and PI3K/AKT signaling pathways. Importantly, erianin synergistically enhanced the anti-tumor efficacy of anlotinib in ATC cells. In vivo, combination therapy with erianin and anlotinib resulted in marked tumor growth suppression and increased apoptosis compared to monotherapies.ConclusionCollectively, our study demonstrates that erianin exerts potent anti-tumor activity in ATC by simultaneously inhibiting the MAPK/ERK and PI3K/Akt signaling pathways, thereby inducing apoptosis and GSDME-dependent pyroptosis. Furthermore, the synergistic interaction between erianin and anlotinib significantly enhances therapeutic efficacy. These findings position erianin as a promising candidate for the treatment of ATC, offering novel therapeutic insights and supporting further clinical investigations.